Ecological and phylogenetic constraints determine the stage of anthetic ovule development in orchids. Issue 12 (5th December 2021) - Mayer, Juliana Lischka Sampaio; Scopece, Giovanni; Barone Lumaga, Maria Rosaria; Coiro, Mario; Pinheiro, Fabio; Cozzolino, Salvatore
Abstract: Premise: Unlike most flowering plants, orchid flowers have under‐developed ovules that complete development only after pollination. Classical studies reported variation in the stage in which ovule development is arrested, but the extent of this variation and its evolutionary and ecological significance are unclear. Methods: Here, we used light microscopy to observe ovule development at anthesis for 39 species not previously studied and surveyed the literature gaining information on 94 orchid species. Tropical and temperate members of all five orchid subfamilies as well as species with contrasting pollination strategies (rewarding versus deceptive) and life forms (epiphytic versus terrestrial) were represented. We analyzed the data using statistical comparisons and a phylogenetic generalized least square (PGLS) analysis. Results: Apostasioideae, the sister to the rest of the orchids, have mature ovules similar to other Asparagales, while under‐differentiated ovules are present in the other subfamilies. Ovule developmental stages showed high variation even among closely related groups. Ovules were more developed in terrestrial than in epiphytic, in temperate than in tropical, and in rewarding than in deceptive pollination orchid species. This latter comparison was also significant in the PGLS analysis. Conclusions: These results suggest that ovule developmental stage in orchids can be shaped by ecological factors, such as seasonality and pollination strategy, and can be selected for optimizing female reproductive investment.